Extrapulmonary Tuberculosis: Clinical and Diagnostic Features and Risk Factors for Early Mortality - Aysert Yıldız, Pınar; Karamanlıoğlu, Dilek; Özger, Hasan Selçuk; Katı, Hakan; Güzel Tunçcan, Özlem; Dizbay, Murat (Acta Medica, 2022)
Objective: The aim of this study is to evaluate patients with EPTB in terms of demographics, anatomic localization, diagnosis and risk factors on early mortality. Materials and methods: The data of 217 inpatients who were followed up with EPTB, between January 2010 and December 2020, were evaluated retrospectively. Patients were followed-up during hospital admission and early mortality was considered. Risk factors on mortality were identified in multivariate analysis using logistic regression model. Results: The median age was 54 (IQR: 37-67) and the rate of male patients was 43.3%. 76 (35%) patients had at least one comorbidity. The most common underlying conditions were diabetes mellitus and immunosuppressive treatment. The most common forms of EPTB were lymph node, bone and CNS. Microbiological findings (ARB and/or TB-culture and/or M. tuberculosis PCR) were positive in 75 patients and histopathological findings (necrotising granuloma with/without pathological caseification) were supportive for diagnosis in 68.2%. The overall mortality rate was 8.5%. In the multivariate analysis, factors independently associated with increased risk of death included advanced age, elevated sedimentation rate above 50mmHg, miliary TB and CNS TB. Conclusion: In conclusion, EPTB is an important health problem in developing countries with significant mortality in specific forms. The most common forms of EPTB are lymph node, bone and CNS TB. The most common underlying conditions are diabetes and immunosuppressive therapy although most patients do not have any underlying diseases. The diagnosis is forcing and a substantial proportion of patients have negative microbiological findings. The diagnosis are based on pathological, radiological and/or clinical findings in patients without definitive microbiological diagnosis. Advanced age, high sedimentation rate and severe forms such as CNS and miliary TB are associated with early mortality.